A comparative study on state reform in the light of the EU and international legal documents and practices: a legal analysis of Turkish regulations on ethics in the government. (14th July 2008) - Yuksel, Cuneyt
In order to modernise and democratise the Turkish administrative system and align it with EU standards, public reform is essential. Good governance, transparency and fight against corruption are indispensable components of a successful reform programme. In this respect, improving transparency, accountability and effectiveness in public service require an effective ethics infrastructure. In the field of accountability and transparency, the law for financial disclosure and combating bribery and corruption dated 1990 and numbered 3628, has a very important role in the fight against corruption in the Turkish public sector. However, the law prohibits accepting gifts from foreign private organisations but does not regulate any prohibition in the case of accepting gifts from Turkish private organisations. This is a very important gap in this law and has to be amended immediately in order to include absolute prohibition with regard to accepting gifts and private interests from both Turkish and foreign nationals and private organisations.